An Empirical Exploration of Psychological Well-Being’s Mediating Influence on Work-Life Balance and Employee Performance in Ghanaian Public Hospitals - Tarik Atan; Hayford Asare Obeng (Asian Journal of Business and Accounting, 2024)
Manuscript type: Research paper Research aims: This study examines how psychological well-being mediates work-life balance and employee performance in Ghana’s public hospitals. Design/Methodology/Approach: The Study used a quantitative design. In AMOS version 23, structural equation modelling was used to analyse the data obtained from 350 participants through a simple random technique. Research findings: This study shows that work-life balance has a strong positive correlation between psychological well-being and employee performance. The study also finds a considerable positive association between psychological well-being and worker performance, and more importantly, the results showed psychological well-being as a mediator in the relationship between work-life balance and employee performance. Theoretical contribution: Empirical evidence supports the Conservation of Resource Theory, making them relevant to Ghana’s public hospitals. Practitioner/Policy implications: These findings add to organizational psychology by emphasizing the importance of supportive work environments, work-life balance, and psychological well-being in healthcare employee performance. Research limitation/Implication: The limited sample size used in this study limits the generalisability of the results. A larger sample size could increase the results’ robustness.